2014
DOI: 10.1186/s40557-014-0028-x
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D status and associated occupational factors in Korean wage workers: data from the 5th Korea national health and nutrition examination survey (KNHANES 2010–2012)

Abstract: ObjectivesVitamin D deficiency is increasing worldwide. However, few studies have attempted to examine the vitamin D status of wage workers and the correlation between vitamin D deficiency and working conditions. Hence, we aimed to evaluate the prevalence of vitamin D deficiency and the association between occupational conditions and vitamin D deficiency among Korean wage workers.MethodsWage workers aged 20–65 years from the 5th Korea National Health and Nutrition Examination Survey (KNHANES 2010–2012; n = 540… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
41
2
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 48 publications
(44 reference statements)
6
41
2
2
Order By: Relevance
“…The prevalence of vitamin D deficiency was highest in managers, professionals, and related workers compared with skilled agricultural, forestry, and fishery workers. These results are consistent with previous studies in Korea [3,28] and other countries [29][30][31]. This result may be because subjects who are classified as managers, professionals, and related workers are usually indoors and do not receive adequate sunlight exposure.…”
Section: Discussionsupporting
confidence: 92%
“…The prevalence of vitamin D deficiency was highest in managers, professionals, and related workers compared with skilled agricultural, forestry, and fishery workers. These results are consistent with previous studies in Korea [3,28] and other countries [29][30][31]. This result may be because subjects who are classified as managers, professionals, and related workers are usually indoors and do not receive adequate sunlight exposure.…”
Section: Discussionsupporting
confidence: 92%
“…The present study showed that higher BMI is associated with lower basal 25OHD in the sample as a whole. This is consistent with the reported in the literature negative association between 25OHD levels and obesity [59][60][61][62][63][64][65][66]. This effect was not evident for each gender group; this may be due to a small sample size in each group.…”
Section: Vitamin D Deficiency and Night Shift Work O R I G I N A L P supporting
confidence: 92%
“…A population study revealed that 25(OH)D deficiency (<20 ng/mL) was present in 69.5% of male and 83.1% of female workers aged 20 to 65 years. [41] This may be related to the high latitude (34°–38° N) of Korea, and reduced levels of time spent outdoors (owing to high educational pressure and indoor working conditions). [4143] Considering the high prevalence of myopia and deficiency of vitamin D in the Korean population, it would be useful to understand the associations of vitamin D deficiency and daily sun exposure time with myopia in this population.…”
Section: Introductionmentioning
confidence: 99%